Effect of Edamame (Glycine max (L.) Merr.) Consumption on Blood Pressure in Patients with Hypertension - Rifaina Fairuz Mulina; Nunung Sri Mulyani (Jurusan Gizi, Poltekkes Kemenkes Aceh, 2026)
Functional foods have emerged as promising non-pharmacological strategies for blood pressure control. Edamame (Glycine max (L.) Merr.) is rich in isoflavones, potassium, magnesium, calcium, and dietary fiber, all of which may contribute to blood pressure reduction. This study evaluated the effect of steamed edamame consumption on blood pressure among hypertensive patients. A quasi-experimental pretest–posttest study with a control group was conducted in June 2025 at the Kandang Community Health Center, Lhokseumawe, Indonesia. Forty hypertensive patients aged 35–60 years were selected through purposive sampling and assigned to intervention (n = 20) and control (n = 20) groups. The intervention group consumed 40 g of steamed edamame daily for seven consecutive days, whereas the control group received steamed soybeans. Blood pressure was measured before and after the intervention using a standardized digital sphygmomanometer. Data were analyzed using paired and independent t-tests with a significance level of p < 0.05. The intervention group experienced significantly greater reductions in systolic and diastolic blood pressure than the control group. Mean systolic and diastolic blood pressure decreased by 11.0 mmHg and 7.85 mmHg, respectively, compared with reductions of 3.55 mmHg and 1.75 mmHg in the control group. Between-group differences were statistically significant for both systolic (7.4 mmHg) and diastolic (6.1 mmHg) blood pressure (p < 0.001). Steamed edamame effectively reduced systolic and diastolic blood pressure among hypertensive patients, suggesting its potential as a locally available functional food and complementary non-pharmacological strategy for hypertension management.